Effect of impurity deposition layer formation on D retention in LHD plasma exposed W. (December 2016) - Oya, Y.; Fujita, H.; Hu, C.; Uemura, Y.; Sakurada, S.; Yuyama, K.; Li, X.; Hatano, Y.; Yoshida, N.; Watanabe, H.; Nobuta, Y.; Yamauchi, Y.; et al.
Highlights: Effect of carbon based mixed-material deposition layer formation on hydrogen isotope retention was studied. Most of the sample surface was covered by a carbon based mixed-material deposition layer formed by plasma experiment campaign. H retention was controlled by the thickness of the carbon-dominated mixed-material deposition layer, indicating that most of H was trapped by this mixed-material deposition layer. The accumulation of low-Z mixed-material layer on the surface of first wall is one of key issues for the determination of hydrogen isotope retention in first wall. Abstract: Effect of carbon based mixed-material deposition layer formation on hydrogen isotope retention was studied. The tungsten (W) samples were placed at four different positions, namely PI (sputtering erosion dominated area), DP (deposition dominated area), HL (higher heat load area), and ER (erosion dominated area) during 2013 plasma experimental campaign in Large Helical Device (LHD) at National Institute for Fusion Science (NIFS), Japan and were exposed to ∼ 4000 shots of hydrogen plasma in a 2013 plasma experimental campaign. Most of the sample surface except for ER was covered by a mixed-material deposition layer formed by plasma experimental campaign, which consisted of carbon, but some metal impurities were contained. For ER sample, He bubbles were formed due to long term He discharge cleaning and He plasma experiments during the plasma experimental campaign. The additional 1 keV D2 + implantation was performed to evaluated the D retention enhancement by plasma exposure. It was found that both of H and D retentions were clearly increased. In particular, the H retention was controlled by the thickness of the carbon-dominated mixed-material deposition layer, indicating most of the H was trapped by this mixed-material deposition layer. It is concluded that the accumulation of low-Z mixed-material layer on the surface of the first wall is one of key issues for the determination of hydrogen isotope retention in first wall.